Reimagining sacred spaces and spiritual leadership: Response to Andrea Baker’s paper Sacred Spaces - Varghese Meloottu, Allan (Missiology, 2025)
Through Andrea Baker’s paper, the realities of abuse and the failure of churches to protect the oppressed are brought closer to our hearts and minds. Baker presents a prophetic call to imagine how Christians may embody the kingdom of God and restore ‘sacred spaces’ in our ecclesial institutions. In light of such a prophetic challenge, as a response, this paper reflects on a couple of aspects that can be pertinent to missiologists. They are: 1) to reimagine how we understand ‘sacred spaces’ and 2) to envision the possibility of holistic leadership development that fosters ‘sacred spaces.’ Consequently, one can discern God’s redeeming presence beyond the four walls of the church while working to restore churches as ‘sacred spaces’ where the love and resurrection power of Jesus Christ become an embodying reality. This paper was read in response to Andrea Baker's plenary address titled ‘Sacred Spaces’ at the Annual Conference of the American Society of Missiology, 2024.